PENCIPTAAN EFEKTIVITAS KOMUNIKASI PEMASARAN MELALUI ADVERTISING LITERACY DENGAN TIE STRENGTH SEBAGAI PEMODERASI - Evelyn Tjiong; Teofilus . (Universitas Ciputra Surabaya, 2022)
Abstract: This research is done to see the effect and pattern on advertising literacy with communication effectiveness thats is moderated by tie strength on start-up business of Universitas Ciputra students. Referring to the condition that occurs is the lack of advertising literacy knowledge that is possessed so that making marketing communication become in effective, therefore through this research can help start-up business to form good business performance. The researcher in this research has gathered successfully by using as many as 140 respondents using purposive sampling and are limited to certain individual, that is, start-up business of 2017 Universitas Ciputra students who use Instagram as marketing tool and have ever made content advertisement design in Instagram. The result that is obtained in this research is there is significant relationship between advertising literacy and communication effectiveness without any moderation variable. However, if the presence of tie strength as moderation variable that makes the relationship between advertising literacy and communication effectiveness become insignificant in order to be able to form communication effectiveness when tie strength becomes independent variable. Keywords: advertising literacy, communication effectiveness, tie strength, start-up business